Implementasi Aplikasi Perawatan Diri Berbasis Self Care untuk Meningkatkan Pengetahuan Pasien Pasca Intervensi Koroner Perkutan - Ali, Abda; Wardani, Ratna (Kolaborasi: Jurnal Pengabdian Masyarakat, 2026)
Introduction: Post Percutaneous Coronary Intervention (PCI) patients require continuous education to support self care knowledge, medication adherence, and follow up visits. Conventional education methods in healthcare settings are often limited by time and accessibility, making digital based educational media a relevant alternative to improve health literacy and patient self management. Objective: To implement the PCI Care application based on Self Care Theory as a digital education media to improve self care knowledge among post PCI patients. Method: This activity used a pre–post test design involving 10 post PCI patients who met the inclusion criteria. The intervention was delivered through the PCI Care application featuring educational content, medication reminders, and follow up schedules. Knowledge was assessed using a 15 item questionnaire administered before and after the intervention. Data were analyzed descriptively. Result: The average knowledge score increased from 40.00 ± 8.25 before the intervention to 85.00 ± 6.10 after the implementation of the PCI Care application (p < 0.001). Participants reported that the application was easy to use via smartphone, contained understandable language, and provided clear information regarding post PCI self care. The educational and reminder features were considered very useful in supporting adherence and enhancing patient understanding of post PCI self care. Conclusion: The implementation of the PCI Care application was proven effective in improving self care knowledge among post PCI patients. Digital education through this application helps patients and families better understand health information and supports adherence to medication and follow-up schedules. PCI Care has the potential to be further developed as a supportive tool in discharge planning and cardiovascular nursing services.